Substantiation of manufacture technology development for the tablets of isosorbide dinitrate with modified release - D. S. Oliinykov; A. H. Kaplaushenko (Zaporozhye State Medical University, 2019)
Isosorbide dinitrate belongs to the group of organic nitrates, the oldest representatives of antianginal drugs, and today is the first-choice drug for purchase and prevention of strokes. High prophylactic efficacy of prolonged forms of nitrates should be noted. The modified-release drugs based on isosorbide dinitrate can combine high pharmacological activity, a long period of therapeutic action, and the absence of serious side effects typical of all nitrate group drugs. The need for modern cardiological preparations with a high level of efficacy and safety creates the need for further development of drugs with modified release, especially for oral administration. The purpose of the work is to choose the concept of a modern solid oral dosage form of isosorbide dinitrate and the technological approach for its implementation. Materials and methods. Data analysis of domestic and foreign scientific literature. Results. The analysis of the advantages and disadvantages of oral dosage forms with traditional immediate and modified release. Modified-release preparations are more technologically sophisticated, but provide a high level of safety, efficacy and convenience for the patient. Conclusion. In the course of the study, the concept of a multidose pellet dosage form was selected to develop modified release isosorbide dinitrate tablets. To obtain pellets containing isosorbide dinitrate, the optimal technological solution is the method of extrusion-spheronization.